Analysis of the Placement and Needs of Elementary School Students Regarding the Environment in Urban Areas - Yubena Abigail Serewati Tambunan; Sapriya (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The topography of each region has its own characteristics. These characteristics will consciously affect every aspect that lives around it. This arises because of the adaptation process experienced by every element of the environment that lives in the region. Because of the differences in topography, the placement of environmental elements in the minds of students and students' needs for the environment in each region will also vary. Based on this, this research was conducted with the research subjects of 5th grade students in an elementary school in Purwakarta Regency. This research uses phenomenological research methods with observation and interviews as data collection techniques. The results found that all subjects were naturally interested in all elements of the environment in their school, they represented this with the adjectives happy, exciting, curious and pity. Regarding students' needs for the environment, three out of five subjects expressed that they needed more knowledge about soil. This includes the replacement of soil function with paving blocks, soil texture, fauna in the soil and soil processes that can make plants grow. It can be concluded that students' placement and needs for their environment depend on the elements of the space they live in